Critical Success Factors of High-Performance Work Systems (HPWS) Practices: Findings from Malaysian SMEs - Husin, Noor Hassanah; Mansur, Nur Naha Abu; Kelana, Beni Widarman Yus (The journal of contemporary issues in business and government, 2021)
This study identified the critical success factors of high-performance work systems (HPWS) in Malaysian manufacturing small and medium enterprises (SMEs). A pilot study was conducted on 30 SMEs from Malaysian manufacturing industries whereby a 55-item questionnaire captured the implementation level of HPWS practices in these industries. Descriptive analysis was performed to analyse the data using Statistical Package for the Social Sciences (SPSS) version 23 software. The findings showed that selective staffing was one of the most critical success factors of HPWS implementation in SME manufacturing industries. This study offers important guidelines for managers in Malaysian SMEs to implement HPWS and to improve SME performance. This research also provides new insight into the critical success factors of HPWS implementation as a tool to enhance employee productivity.